Formulation of Goat Milk Synbiotic Kefir with Beet Extract and Dragon Fruit as an Alternative Drink for Obese Patients: Crude Fiber Content and pH - Indah Nuraeni; Nur Wijayanti; Budi Sustriawan; Koernia Nanda Pratama (Program Studi Teknologi Pangan Fakultas Pertanian UNSOED, 2026)
Background: Obesity is a global health problem that requires innovative therapeutic approaches, one of which is through modulation of the gut microbiota using synbiotic products. Purpose: This study aimed to formulate and analyze the effect of banana peel flour proportion (as a prebiotic) and beetroot and dragon fruit extracts on crude fiber content and pH of goat milk synbiotic kefir. Method: The experimental design used was a factorial Randomized Block Design (RBD) with two factors: banana peel flour concentration (1% and 2%) and beetroot:dragon fruit extract combination concentration (5%, 10%, 15%). Result: The results showed that the interaction of the two factors significantly affected crude fiber content (p=0.02), with the highest value (5.44 ± 1.56%) achieved in treatment added of 2% banana peel flour and 15% extract, but had no significant effect on pH value (p=0.199), which ranged from 3.37–4.09. It was concluded that the formulation of synbiotic kefir with the addition of banana peel flour, beetroot, and dragon fruit extract has the potential to be developed as a high-fiber functional beverage for obese individuals.